القيم الصحية المتضمنة في الكتاب المدرسي للتربية المدنية للمرحلة الابتدائية - كريمه زكور فرحات; فريال بالهادف (جامعة الوادي - University of Eloued, 2025)
"هدفت الدراسة إلى الكشف عن مستوي تضمين القيم الصحية في الكتاب المدرسي للتربية المدنية للمرحلة التعليم الابتدائي، ولتحقيق أهداف الدراسة تم اعتماد المنهج الوصفي التحليلي، وتم إعداد أداة للدراسة تمثلت في أداة تحليل محتوى. والتي قامت الباحثتين بإعدادها، حيث تكونت من (05) قيم رئيسية لتتفرع عنها (42) قيم فرعية من القيم الصحية، وقد عرضت على مجموعة من المحكمين المتخصصين، حيث تم الاتفاق على كل فقرات أداة التحليل. قد استخدمت الباحثتين في هذه الدراسة الأساليب الإحصائية التالية: ــ التكرارات والنسب المئوية، لمعرفة مدى تضمين الكتاب للقيم الصحية. ــ معادلة كوبر لقياس الصدق. ــ معادلة هولستي لقياس ثبات أداة التحليل. من خلال تحليل محتوى الكتاب تبين تضمين القيم الصحية بالترتيب الآتي: ــ المرتبة الأولى قيمة الصحة الغذائية (40%). ــ المرتبة الثانية قيمة نظافة المحيط (28%). ــ المرتبة الثالثة قيمة النظافة الشخصية (24%). ــ المرتبة الأخيرة قيمة الصحة الجسمية (08%). ــ غياب تام لقيمة السلامة من الأخطار المنزلية (00%)." "This study seeks to examine the extent to which health-related values are embedded in the civic education textbook used at the primary education level. To achieve this objective, the researchers employed a descriptive analytical approach and developed a content analysis tool specifically designed for this purpose. The tool, constructed by the two researchers, encompassed five overarching health values, which were further subdivided into 42 sub-values. The instrument was submitted to a panel of subject-matter experts, who confirmed the validity and appropriateness of all its components The researchers employed the following statistical methods in this study: Frequencies and percentages to determine the extent to which the textbook includes health values. Cooper’s formula to measure the validity of the analysis tool. Holsti’s formula to assess the reliability of the analysis tool. The analysis of the textbook content revealed the following distribution of health values: - First rank: Nutritional health (40%) - Second rank: Environmental cleanliness (28%) - Third rank: Personal hygiene (24%) - Fourth rank: Physical health (8%) - Not represented: Safety from domestic hazards (0%)."
مذكرة ماستر قسم علم النفس وعلوم التربية تخصص إرشاد وتوجيه
Keywords: مرحلة التعليم الابتدائي; التربية المدنية; الكتاب المدرسي; القيم الصحية; القيم; Values; Health Values; Textbook; Civic Education; Primary Education Stage